(untitled) - Pivarnik-Nova, Denise (Hoboken, NJ, 2005)
Is the dreaded SAT Writing Test weighing heavily on your mind? Get in shape to tackle it with this in-depth writing workout. In comfortable CliffsNotes® style, you'll get the information you need to improve your score-fast! Part I: Introduction An overview of the new SAT exam An overview of the Writing Test, including the essay and multiple-choice questions A diagnostic test Part II: The Essay and Verbal Review Essay writing skills, from topic sentences to conclusions Rules to review and remember Sample essays with critiques on why they are good and how they could be better Review of grammar and usage you need to know Practice with multiple-choice questions Practice writing essays Part III: Practice Exams Four full-length practice tests with complete answers and explanations Two model essay responses per test, each with suggested scoring and detailed analysis
Keywords: English language,SAT (Educational test),Anh ngữ,SAT (Giáo dục kiểm tra); Composition and exercises,Examinations,Thành phần và bài tập,Kỳ thi